SmartCart Project: Adding Intelligence to Shopping Carts - Silva, Carlos Eduardo Bezerra Mendes; Lima, Marcos Eduardo Araújo de; Souza, Thiago José Alves de; Paula, João Pedro Mafaldo de; Silva Júnior, Marcondes Ricarte da; Teixeira, João Marcelo Xavier Natário (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2023: Anais do XX Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2023.236510, 2023)
The retail sector has been experiencing a transformation in which the incorporation of technologies into the shopping process is becoming increasingly common, aiming to provide a better experience for consumers. In this context, this paper seeks to propose a solution that uses embedded hardware in shopping carts to enhance the shopping experience, primarily speeding up the payment process by allowing customers to scan the barcodes of desired products without having to face long queues. It also aims to provide a supermarket map, indicating the current position of the cart. To achieve these objectives, computer vision was used to recognize QR codes attached to the ceiling. Following this methodology, satisfactory results were obtained, with paths for improvement and possible changes to be made in the project to achieve greater accuracy in estimating the cart’s location.